Utility of laboratory markers in evaluating for acute compartment syndrome in the emergency department - Gregory S. Weingart; Phillip Jordan; Kei‐Lwun Yee; Lauren Green (Journal of the American College of Emergency Physicians Open)
Abstract Background Acute compartment syndrome is diagnosed by clinical examination with the aid of direct compartmental measurement. Previous work suggested using several laboratory markers that may suggest ongoing acute compartment syndrome in hospitalized patients. Serum creatinine kinase (CK) levels >4000 U/L, chloride (Cl) levels >104 mg/dL, and blood urea nitrogen (BUN) levels <10 mg/dL were found to have 100% association with the diagnosis of acute compartment syndrome. This strategy has not been studied in emergency department (ED) patients. Methods A retrospective chart review of all patients diagnosed with acute compartment syndrome of the upper and lower extremity or tibia/fibula fracture was performed from 13 EDs between February 22, 2008 and October 1, 2018. Serum values were collected for each patient: CK, sodium (Na), potassium (K), Cl, bicarbonate (HCO3), glucose, BUN, creatinine (Cr), calcium, lactic acid (LA), and ionized calcium (iCa). A control group composed of patients without acute compartment syndrome who had tibia and/or fibula fractures was analyzed to compare with our cohort. Results We identified 930 patients who meet inclusion criteria (389 acute compartment syndrome patients and 541 tibia/fibula fracture patients). Sex and ethnicity were similar in each population. A majority of the patients were evaluated at EDs without a trauma center designation. Using univariate modeling, HCO3, CK, iCa, Cr, BUN, and K values were found to be individual significant predictors of acute compartment syndrome (P < 0.05). Multivariate regression models found that HCO3 and Cr were significant predictors of acute compartment syndrome with a C‐statistic of 0.77. The Valdez model had a prediction accuracy of 0.52 and a specificity of 99.2% but had a sensitivity of only 2.9%. Conclusion Our model demonstrates that use of serum biomarkers in the ED does aid in the diagnosis of acute compartment syndrome in patients in the ED with 99.2% specificity but has a sensitivity of only 2.9%. Further research and prospective evaluation of serum markers are needed.